Pengaruh Literasi Keuangan, Kepemimpinan Transformasional, dan Akses Teknologi Terhadap Efisiensi Anggaran dan Pelayanan Publik - Desak Putu Putri Maharani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study explores the influence of financial literacy, transformational leadership, and access to technology on budget efficiency and quality of public services in Indonesia. With a quantitative approach using Structural Equation Modeling (SEM), this study involved a saturated sample of relevant public sector organizations. The results of the analysis show that financial literacy has a significant effect on budget efficiency, where mastery of financial information supports more appropriate decision making. In addition, transformational leadership has been shown to encourage innovation and motivation in the work environment, which in turn improves the quality of public services. Access to technology acts as a catalyst that strengthens the relationship between financial literacy and public services, increasing transparency and efficiency of the administrative process. The synergy between these three elements creates more responsive and accountable governance, providing a positive impact on society. These findings emphasize the importance of integrating financial literacy, innovative leadership, and technology in improving the efficiency and effectiveness of public sector management. This study is expected to be a reference for policy makers in designing better and more sustainable resource management strategies.